Two cofactors and cytoplasmic chaperonin are required for the folding of alpha- and beta-tubulin. - Gao, Y (1993)
Though the chaperonins that mediate folding in prokaryotes, mitochondria, and chloroplasts have been relatively well characterized, the folding of proteins in the eukaryotic cytosol is much less well understood. We recently identified a cytoplasmic chaperonin as an 800-kDa multisubunit toroid which forms a binary complex with unfolded actin; the correctly folded polypeptide is released upon incubation with Mg-ATP (Y. Gao, J. O. Thomas, R. L. Chow, G.-H. Lee, and N. J. Cowan, Cell 69:1043-1050, 1992). Here we show that the same chaperonin also forms a binary complex with unfolded alpha- or beta-tubulin; however, there is no detectable release of the correctly folded product, irrespective of the concentration of added Mg-ATP and Mg-GTP or the presence of added carrier tubulin heterodimers with which newly folded alpha- or beta-tubulin polypeptides might exchange. Rather, two additional protein cofactors are required for the generation of properly folded alpha- or beta-tubulin, which is then competent for exchange into preexisting alpha/beta-tubulin heterodimers. We show that actin and tubulins compete efficiently with one another for association with cytoplasmic chaperonin complexes. These data imply that actin and alpha- and beta-tubulin interact with the same site(s) on chaperonin complexes.